Immune response to Escherichia coli B surface antigens. - Taplits, M (1979)
The cell surface antigens of Escherichia coli B were investigated. We found that mice immunized with live bacteria responded with an immune response directed mainly against the protein structure of the cell surface. The lipopolysaccharide component of the bacterium was immunogenic, but its contribution to the overall response was only secondary. It is suggested that when considering the immune response to gram-negative bacteria, more attention should be given to the protein antigens.